Ella on the outside - Howe, Cath (Nosy Crow, 2018)
"Ella is the new girl at school. She doesn't know anyone and she doesn't have any friends. And she has a terrible secret. Ella can't believe her luck when Lydia, the most popular girl in school, decides to be her new best friend - but what does Lydia really want? And what does it all have to do with Molly, the quiet, shy girl who won't talk to anyone? A gripping story of lies, friendship, and blackmail..." --Publisher description